Effect of Fiber Orientation (0° and 90°) on the Tensile Properties of Abaca Fiber-Reinforced Epoxy Composites - Abraham Fatbinan; Dwi Hartini; Benedictus Dwi Mardwianta; Buyung Junaidin; Elisabeth Anna Prattiwi; Djarot Wahju Santoso (Vortex, 2026)
Abaca fiber is a natural reinforcement material with considerable potential for environmentally friendly and lightweight structural applications. This study aims to investigate the effect of fiber orientation (0° and 90°) on the tensile properties of abaca fiber-reinforced epoxy composites. The composites were fabricated using the hand lay-up method followed by vacuum bagging, with a fiber-to-matrix volume fraction of 50:50. Tensile testing was conducted in accordance with ASTM D3039 standards using a Universal Testing Machine (UTM).The results indicate that fiber orientation has a substantial influence on the mechanical performance of the composites. Specimens with a 0° fiber orientation exhibited a significantly higher average tensile strength of 102.51 MPa and an elastic modulus of 889.30 MPa. In contrast, specimens with a 90° orientation showed much lower values, with an average tensile strength of 4.97 MPa and an elastic modulus of 77.18 MPa. This difference is attributed to the alignment of fibers parallel to the loading direction in the 0° orientation, allowing efficient load transfer through the fibers. Meanwhile, the 90° orientation relies primarily on the matrix and fiber–matrix interface to resist tensile loading.Failure analysis revealed that the 0° specimens were dominated by fiber breakage and delamination, whereas the 90° specimens exhibited matrix-dominated failure mechanisms such as matrix cracking and interfacial debonding. In addition, the stress–strain curve characteristics confirmed that specimens with a 0° orientation possessed higher stiffness and lower deformation than those with a 90° orientation. These findings highlight the critical role of fiber orientation in determining the tensile performance of natural fiber-reinforced composites and confirm that fiber alignment parallel to the loading direction provides superior mechanical properties.The results of this study are expected to contribute to the development of sustainable composite materials for lightweight structural applications, particularly in aerospace engineering and unmanned aerial vehicle (UAV) structures.